The Effect of Individual Innovation and Emotional Intelligence on Positive Organizational Behavior - Nuri Berk Güngör,; Zulbiye Kaçay,; Fikret Soyer, (Journal of Educational Issues, 2024)
The purpose of this research is to examine the effects of individual innovation and emotional intelligence levels on organizational behavior of the participants working in the Provincial Directorate of Youth and Sports. The study group of the research consists of 77 female (38.7%) and 122 male (61.3%) participants working in the Provincial Directorate of Youth and Sports. As a data collection tool in the research; Individual Innovation, Emotional Intelligence and Positive Organizational Behavior Scales were used. The participants drew a high level of innovative profile; It can be stated that he has an above-average level of emotional intelligence and organizational behavior. According to the results of the research; A significant, positive and moderate relationship was found between individual innovation, emotional intelligence and organizational behavior. In addition; It can be said that 53% of organizational behavior is explained by individual innovation and emotional intelligence characteristics.